Direct and Indirect Visualization of Bacterial Effector Delivery into Diverse Plant Cell Types during Infection. Issue 7 (9th June 2017) - Henry, Elizabeth; Toruño, Tania Y.; Jauneau, Alain; Deslandes, Laurent; Coaker, Gitta
Abstract : The GFP strand system enables spatial and temporal visualization of bacterial effector delivery during infection. Abstract: To cause disease, diverse pathogens deliver effector proteins into host cells. Pathogen effectors can inhibit defense responses, alter host physiology, and represent important cellular probes to investigate plant biology. However, effector function and localization have primarily been investigated after overexpression in planta. Visualizing effector delivery during infection is challenging due to the plant cell wall, autofluorescence, and low effector abundance. Here, we used a GFP strand system to directly visualize bacterial effectors delivered into plant cells through the type III secretion system. GFP is a beta barrel that can be divided into 11 strands. We generated transgenic Arabidopsis thaliana plants expressing GFP1-10 (strands 1 to 10). Multiple bacterial effectors tagged with the complementary strand 11 epitope retained their biological function in Arabidopsis and tomato ( Solanum lycopersicum ). Infection of plants expressing GFP1-10 with bacteria delivering GFP11-tagged effectors enabled direct effector detection in planta. We investigated the temporal and spatial delivery of GFP11-tagged effectors during infection with the foliar pathogen Pseudomonas syringae and the vascular pathogen Ralstonia solanacearum . Thus, the GFP strand system can be broadly used to investigate effector biology in planta.